Dari Terestrial ke Digital: Pergeseran Praktik Siaran Radio di Era Digital - Astuti, Budhi Widi; Abrar, Ana Nadhya; Irawanto, Budi (Universitas Gadjah Mada, 2026)
Digital transformation has brought the internet and social media into today's new media. Their presence has brought changes to the broadcasting industry, including radio broadcasting media, and has impacted media consumption shifts among listeners, as well as a decline in radio advertising. This forces radio operators to take strategic actions for the sustainability of radio. This paper aims to explain the shift in radio media consumption behavior and the strategies adopted by radio operators in facing various changes. Media convergence theory serves as the basis for analyzing these dynamics. To answer the research objectives, the researcher applied two research methods: quantitative and qualitative. Quantitative data collection was carried out by distributing questionnaires to obtain data from respondents from public, local, private, and community radio broadcasters in several regions in Indonesia. Furthermore, a qualitative method was chosen as the approach in the case study. Qualitative data collection was conducted by interviewing five selected radio operators. The results of the study indicate that digital transformation has shifted radio consumption and changed radio broadcasting practices, making media convergence one way to survive in this digital era.